Child and adolescent mental health - Maurer, Martin H. (IntechOpen, 2017)
In the present volume, we collected state-of-the-art chapters on diagnosis, treatment, and social implications. The first section describes diagnostic processes. It describes a reevaluation of projective techniques, a new clinical tool in psychotraumatology, the foundations of the framing technique, and an overview on integrative approaches. The second section focuses on new developments in the field with special emphasis on culture-specific contexts. From parenting of adolescents in India to the influence of poverty on mental health issues in Mexico, as well as the use of marijuana and Internet addiction, some of the most important fields are highlighted. The third section concentrates on therapy. It shows how to react to bullying and reviews the use of antidepressants in children and adolescents